Ferroptosis Induction in Pentylenetetrazole Kindling and Pilocarpine-Induced Epileptic Seizures in Mice - Xiao‐Yuan Mao; Hong-Hao Zhou; Weilin Jin (2019)
Epilepsy is a serious neurological disorder and is characterized by recurrent and unprovoked seizures. A critical pathological factor in the seizure genesis is neuronal loss. Until now, apart from the known regulatory cell death pathways, ferroptosis is a newly discovered type of cell death with the features of iron accumulation and the excessive production of lipid reactive oxygen species (ROS). In our present work, it was illustrated that ferroptosis occurs in murine models of pentylenetetrazole (PTZ) kindling and pilocarpine (Pilo)-induced seizures. In both of these seizure models, treatment with ferroptosis inhibitor ferrostatin-1 (Fer-1) efficiently alleviates seizures. This was achieved through elevated levels of glutathione peroxidase 4 (GPX4) and glutathione (GSH) as well as inhibitions of lipid degradation products including 4-hydroxynonenal (4-HNE) and malonaldehyde (MDA), iron accumulation, and PTGS2 mRNA in the hippocampus. It was concluded that ferroptosis is involved in seizure genesis in PTZ- and Pilo-treated mice, while the suppression of ferroptosis mitigates PTZ kindling, and Pilo-induced seizures in mice.